The review of geohazards in Xiaolongtan Lignite Deposite. Issue 1 (November 2019) - Yang, Shuran; Huang, Qianrui; Cheng, Xianfeng; Qi, Wufu; Zhang, Xiangqun; Xiang, Yungang; Zhang, Jiansheng
Abstract: This paper reviews the various aspects of the Xiaolongtan Lignite deposit mine and summarizes the geological disasters of Buzaoba pit, Xiaolongtan pit and Xindenger dump, including landslides, floods, bench erosion, the physical-mechanical changes caused by spring water and lignite spontaneous combustion.